Esophageal stricture assessment by esophagogram: A pictorial review of differential diagnosis - Rockenbach, Marcio Aloisio Bezerra Cavalcanti; Pedrollo, Ivan Morzoletto; Maciel, Antonio Carlos (Clinical and Biomedical Research, 2019)
The purpose of this article is to review the most frequent conditions associated with esophageal strictures on esophagogram. The most common causes include caustic ingestion, radiation therapy, malignancy, extrinsic compression, gastroesophageal reflux disease, infectious esophagitis, systemic diseases and membranes and rings. Adequate characterization of the stricture is necessary for formulation of the best diagnostic hypothesis and can be used to distinguish between malignant and non-malignant conditions. Keywords: Esophageal diseases; esophageal stenosis; esophagus; esophageal neoplasms; esophageal achalasia; radiography; radiology; radiotherapy